THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON STOCK RETURNS IN PROPERTY AND REAL ESTATE COMPANIES ON THE IDX - Delia Ananda; Ghazali Syamni; Zulfan; Wardhiah (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the influence of internal and external factors on stock returns of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The internal factors examined include Return on Assets (ROA), Earnings Per Share (EPS), and Debt to Equity Ratio (DER), while the external factors consist of inflation, interest rates, and exchange rates. A quantitative approach was employed, using secondary data obtained from annual financial reports and national macroeconomic indicators. Data analysis was conducted using panel data regression, with model selection determined through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results show that partially, ROA and EPS have a positive and significant effect on stock returns, while DER has a negative but insignificant effect. Among external factors, inflation and interest rates negatively affect stock returns but are not statistically significant, whereas exchange rates exhibit a negative and significant influence. These findings support the Efficient Market Hypothesis and Arbitrage Pricing Theory, indicating that both internal and external variables collectively affect stock performance in the capital market. This study provides valuable insights for investors in evaluating financial fundamentals and macroeconomic conditions for better investment decision-making.